ISU-ISU PERMASALAHAN ADMINISTRASI PUBLIK DI INDONESIA - putri, dina amalia; M. Fachri Adnan (Merwin Publisher, 2024)
Public administration is the art and science of organizing public administration and task execution procedures. This research aims to explore how many public administration issues are still waiting to be clarified, researched, analyzed, studied scientifically, and found solutions to solve them in a sustainable and multidisciplinary manner. This research was conducted using the literal development method which involves the use of Public Administration. This study states that the New Public Service Perspective in Good Governance is the most appropriate for the current conditions in managing public service problems in Indonesia.